Promoting Environmental Safety CultureThrough Education: Global Trends AndPerspectives - Mukhtarova Lobar Abdimannabovna (Euro Asian Journal Publishing, 2026)
At the contemporary stage of global development, guaranteeing an environmentally safe living space for humanity has become an issue of paramount importance. The growing scale of environmental pollution and the weakening of the balanced interaction within the “Nature–Society–Human” system require comprehensive reflection and scientifically grounded responses. In this context, fostering students’ environmental safety culture through modern interdisciplinary approaches is regarded as an essential demand of the present era. This article explores the nature of global environmental challenges by focusing on the conceptual foundations of “ecology,” “security,” “culture,” and “environmental safety culture.” Special attention is given to identifying the distinctive characteristics of environmental safety and substantiating the necessity of scientific inquiry based on a robust theoretical and methodological framework.
Keywords: environmental safety; ecology; security; culture